2020
DOI: 10.1177/0887403420903376
|View full text |Cite
|
Sign up to set email alerts
|

The Right to a Good Defense: Investigating the Influence of Attorney Type Across Urban Counties for Juveniles in Criminal Court

Abstract: Juvenile defendants in criminal court represent an especially vulnerable group for whom quality legal representation is critical. While some juvenile defendants are able to obtain private counsel, indigent defendants are provided an attorney by the government. One long-standing concern is that these court-appointed attorneys are less effective. Using data on juveniles in criminal court across 37 large, urban counties, the present study examines conviction and sentencing outcomes by comparing private counsel, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…2. One recent study found that the effect of legal representation on criminal court convictions was not moderated by county urbanism (Zane et al, 2021) 3. Unlike race and sex, age is not clearly an extra-legal variable in the context of juvenile court, where age may be connected to attributions of culpability and potential for reform (see Mears et al, 2014).…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. One recent study found that the effect of legal representation on criminal court convictions was not moderated by county urbanism (Zane et al, 2021) 3. Unlike race and sex, age is not clearly an extra-legal variable in the context of juvenile court, where age may be connected to attributions of culpability and potential for reform (see Mears et al, 2014).…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“… 2. One recent study found that the effect of legal representation on criminal court convictions was not moderated by county urbanism (Zane et al, 2021) …”
mentioning
confidence: 99%